The importance of bacteria of the genus Bifidobacterium in intestinal microbiocenosis - Baiguzhina , Zh.S.; Hasenova, A.E.; Yeleupayeva, Sh.K.; Dinmuhamedova, A.S.; Alzhanova, G.S.; Aizman , R.I.; Bazarbayeva, S.M.; Khamzina, S.R.; Zhumagaliyeva, Zh.Zh. (Fundamental and Experimental Biology, 2024)
Bifidobacteria are the most common microorganisms in the intestines of healthy breastfed children. The genus Bifidobacterium includes bacteria characterized by probiotic properties, such as the induction of immunomodulators, increasing the nutritional value of products due to the assimilation of substrates that are not broken down by the host, anticarcinogenic activity, synthesis of vitamins, production of antimicrobial drugs, which contribute to the promotion of health. Bifidobacteria demonstrate physiological and genetic characteristics including adhesion to the intestinal epithelium, as well as metabolism of glycans in the host body. Multitrophic interaction is formed based on various mechanisms of substrate recognition in the surrounding environment and the transmission of molecular and genetic information, which contributes to survival in the human gastrointestinal tract. Representatives of the Bifidobacterium bifidum species constitute a dominant taxon among bifidobacteria, demonstrating significant probiotic properties and extensive potential for the treatment and prevention of various diseases. Currently, a large number of Bifidobacterium bifidum species have been sequenced, which are of interest to medicine, biotechnology, and agriculture. Their genetic strategies for colonizing and persisting in the human intestine have been identified. Cross-interaction mechanisms of Bifidobacterium bifidum with the host and other microorganisms have been demonstrated using various structures. In this review, we discuss current knowledge about the biology of the genus Bifidobacterium, including the biological characteristics of Bifidobacterium bifidum species, which exhibit specific adaptations to the human intestine.